Canagliflozin for Prevention of Cardiovascular and Renal Outcomes in type2 Diabetes: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Tian, Lei; Cai, Yuzi; Zheng, Huijuan; Ai, Sinan; Zhou, Mengqi; Luo, Qian; Tang, Jingyi; Liu, Weijing; Wang, Yaoxian (Frontiers in Pharmacology, 2021)
Abstract Objective: We aimed to evaluate the efficacy of canagliflozin for the treatment of specific cardiovascular and renal outcomes in Type 2 diabetes mellitus (T2DM) patients by means of a systematic review and meta-analysis. Methods: We performed comprehensive searches of PubMed, the Cochrane Library, and Embase for randomized, placebo-controlled trials of the treatment of T2DM with canagliflozin that were published to 28 September 2020. The cardiovascular outcomes recorded were cardiovascular mortality, heart failure, myocardial infarction, and stroke. The renal composite outcomes recorded were end-stage renal disease (ESRD), renal death. The data for the principal cardiovascular outcomes, ESRD, and renal death were pooled and expressed as Hazard ratios (HRs) with 95% confidence intervals (CIs). Two reviewers independently selected the trials and extracted the data. Results: The meta-analysis showed that canagliflozin significantly reduced the risk of heart failure in T2DM by 36% (HR 0.64, 95% CI 0.53 to 0.77, p=0.000). The effects of canagliflozin on non-fatal myocardial infarction or non-fatal stroke (HR 0.84, 95% CI: 0.76 to 0.93, p=0.001), cardiovascular mortality (HR 0.84, 95% CI 0.72 to 0.97, p=0.021), and myocardial infarction (HR 0.84, 95% CI 0.70 to 1.00, p=0.045) in patients with T2DM were relatively small, only reducing the risks by 16%. In addition, canagliflozin only reduced the risk of stroke in T2DM patients by 13% (HR 0.87, 95% CI 0.71 to 1.06, p=0.166).Moreover, canagliflozin significantly reduced the risk of the composite renal event of ESRD or renal death by 36% (HR 0.64, 95% CI 0.54 to 0.75, p=0.000). Conclusions: This meta-analysis suggests that canagliflozin protects against cardiovascular and renal outcomes in patients with T2DM.